NON LITERAL MEANING IN EDGAR ALLAN POE SELECTED POEMS - Okky Agastya and Sri Juriati Ownie (LINGUISTICA, 2015)
This research is focused on non literal meaning used in Edgar allan Poe SelectedPoems : Annabel Lee, The Raven, Alone, A Dream Within a Dream and A Valentine.The research was conducted by using descriptive qualitative method. The data wascollected from every poems of Edgar Allan Poe. The findings of the research showthat there are 76 lines of non literal meanings which classified into seven types nonliteral meaning. They are Metaphor (42), Hyperbole (15), Metonymy (12),Synecdoche (7), and there is no Litotes (0) and Irony (0). The most dominant type ofnon literal meaning that used in selected poems is Metaphor with 55,3%. It meansthat most of Edgar Allan Poe Works is fulfilled of the beautiful word that created bycomparing two unrelated things that make a new word. Sometimes that new word ishard to find the real meaning because it can be interpreted differently according theimagination of each people.